Youth labour flows and exits from unemployment in Great Recession - Vladislav Flek; Martin Hala; Martina Mysikova (Charles University in Prague, Institute of Economic Studies (IES), 2015)
Using Spain and the Czech Republic as examples of two EU countries with remarkably different youth labour market performance, we apply a gross flow analysis based on EU-SILC longitudinal data. While in Spain increases in youth unemployment rate are driven mostly by young people losing their jobs, in the Czech Republic, this is mainly due to new labour market entrants who failed to find a job. Furthermore, the analysis of flow transition rates suggests that the job-loss rates of young workers are persistently higher than those established for prime-age workers. But the analogous result applies, though less uniformly, also to the jobfinding rates. Survival functions estimates point to prolonged unemployment duration and increasing long term unemployment, while both these tendencies apply relatively more to the young unemployed. Proportional hazard models generally indicate that shorter unemployment spells are more likely to be terminated by finding a job in comparison with those spells lasting for more than one year, while the hazard ratios for duration intervals under one year are typically higher for prime-age unemployed. Finally, we examine education, gender, household size, etc. as determinants of exits from unemployment, with uniform evidence found for tertiary education only.
Keywords: E24; J6; 330; flow transition rates; gross labour market flows; hazard function; survival function; unemployment